2005
DOI: 10.1079/sum2005351
|View full text |Cite
|
Sign up to set email alerts
|

A soil carbon and land use database for the United Kingdom

Abstract: The compilation of a database of soil carbon and land use is described, from which models of soil carbon dioxide emissions across the United Kingdom (UK) can be run. The database gives soil organic carbon, sand, silt and clay contents and bulk densities weighted to reference layers from 0 to 30 cm and from 30 to 100 cm depths. The data are interpolated from information on soil types and land use on a 1 km grid across the UK and are used to estimate soil carbon stocks. For 1990, the baseline year for the Kyoto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(209 citation statements)
references
References 4 publications
11
180
0
Order By: Relevance
“…The key principles in this respect are to avoid loss of carbon from the soil and to manage the application of nutrients in fertilizers and manure to maximize uptake by plants. In terms of soil, the type of soil is closely associated with the amount of carbon it contains and there is a huge variability across the UK with Scotland holding around a half of the organic carbon content of soils in Great Britain (Bradley et al, 2005). Recent research has shown that there is little change in soil carbon under permanent pasture (Hopkins et al, 2008), with the major changes being related to changes in land use (Smith, 2008).…”
Section: Gill Smith and Wilkinsonmentioning
confidence: 99%
“…The key principles in this respect are to avoid loss of carbon from the soil and to manage the application of nutrients in fertilizers and manure to maximize uptake by plants. In terms of soil, the type of soil is closely associated with the amount of carbon it contains and there is a huge variability across the UK with Scotland holding around a half of the organic carbon content of soils in Great Britain (Bradley et al, 2005). Recent research has shown that there is little change in soil carbon under permanent pasture (Hopkins et al, 2008), with the major changes being related to changes in land use (Smith, 2008).…”
Section: Gill Smith and Wilkinsonmentioning
confidence: 99%
“…Several studies have estimated SOC stocks on a large scale by using national and global soil maps and a certain amount of representative soil profiles, or by combining soil and land cover spatial data sets (Batjes, 1996(Batjes, , 2005Batjes and Dijkshoorn, 1999;Arrouays et al, 2001;Morisada et al, 2004;Bradley et al, 2005;Leifeld et al, 2005). Commonly, inventories are based on a combination of soil land use mapping units and assignment of mean SOC values from soil profiles, which makes it possible to determine patterns in SOC variability related to soil and land use features.…”
Section: Muñoz-rojas Et Al: Organic Carbon Stocks In Mediterraneamentioning
confidence: 99%
“…This paper suggests that the maximum carbon capture potential of urban soils using biochar and inorganic carbon accumulation is approximately 7 Mt C y -1 , which is over three times the quantity of carbon released during land use change from forest, cropland and grassland soils to UK cities (DEFRA, 2009). The maximum potential of organic carbon accumulation is unknown, but tree planting can sequester 0.6-0.8 kg C m -2 y -1 into biomass (Read et al, 2009), and carbon storage in UK woodlands soils is estimated to be 25 kg m -2 to 1m depth (Bradley et al, 2005), which appears to be considerably higher than values reported for urban woodlands (Table 1). This suggests there may be potential to manage urban woodlands to achieve higher soil sequestration, but further studies are required to establish this.…”
Section: Implications For Engineers and Plannersmentioning
confidence: 39%
“…Within the UK, there is a paucity of data on soil carbon storage in towns and cities, and where estimates have been made, they have been based on rather crude assumptions. For example, carbon concentrations in suburban areas were assumed to be half that found in typical pasture soils (Bradley et al, 2005), an assumption not supported by current data (Table 1). Research now being conducted in the city of Leicester is measuring soil and vegetation carbon storage and sequestration to help inform management of greenspaces in UK urban areas (www.4mfootprint.org).…”
Section: Organic Carbon In Urban Soilsmentioning
confidence: 96%
See 1 more Smart Citation